(untitled) (UNED Research Journal, 2023)
Introduction: Studies on malaria vector surveillance are useful for evidence-based control in specific communities. Such studies are lacking in Malete, a rapidly growing peri-urban community in Nigeria. Objective: To assess sibling species identity, human blood indices, and Plasmodium falciparum transmission risks by Anopheles mosquitoes, in Malete. Methods: I collected endophilic mosquitoes quarterly from inhabited houses using the pyrethrum spray catch technique. I identified the mosquitoes, and probed for the presence of human blood and P. falciparum, using standard PCR and ELISA methods, respectively. Results: Anopheles mosquitoes (90%) were the most abundant compared to Culex (10%) and Mansonia (0,5%). Specifically, A. gambiae (85%) were predominant over A. coluzzii (11%) and A. arabiensis (3%). The Anopheles sibling species had generally high human blood indices (≥0,82). However, A. gambiae man-biting rates (0,92-3,64) were higher than A. coluzzii (0-0,84) and A. arabiensis (0-0,27). Plasmodium falciparum sporozoite infection (3%) was found only in A. gambiae. Conclusion: While P. falciparum infection was 3%, long-lasting insecticidal nets should be deployed for control in Malete, particularly of A. gambiae.